The SGLT2 inhibitor empagliflozin might be a new approach for the prevention of acute kidney injury - Chu, Chang; Hocher, Berthold (Kidney & blood pressure research, 2019)
Three randomized control trials (Canagliflozin Cardiovascular Assessment Study, Empagliflozin Cardiovascular Outcome Event Trial in Type 2 Diabetes Mellitus Patients [EMPA-REG OUTCOME], and Dapagliflozin Effect on Cardiovascular Events-Thrombolysis in Myocardial Infarction 58 [DECLARE-TIMI 58]) showed that the sodium-glucose co-transporter 2 (SGLT2) inhibitors, originally developed as glucose-lowering drugs, are associated with a lower rate of adverse renal outcomes, such as need for renal replacement therapy, doubling of serum creatinine, and loss of glomerular filtration rate (GFR) compared to those in placebo groups. Besides, canagliflozin and empagliflozin also showed a lower risk of progression to macroalbuminuria. The EMPA-REG OUTCOME trial and DECLARE-TIMI 58 trial also indicated that these SGLT2 inhibitors might have beneficial effects on the prevention of acute kidney injury. The United States Food and Drug Administration (FDA) warned of the risk of acute kidney injury for canagliflozin and dapagliflozin. We compared canagliflozin, empagliflozin, and dapagliflozin with respect to chemical structure and pharmacological properties, to explain the observed differences in preventing acute kidney injury, and put forward the hypotheses of the potential mechanisms of different effects of SGLT2 inhibitors on acute kidney injury. Given the raising clinical use of SGLT2 inhibitors, our review should stimulate further basic science and clinical studies in order to definitively understand the role of SGLT2 inhibitors in acute kidney injury. A weakness of the clinical data obtained so far is the fact that the statements concerning acute kidney injury are just based on safety data - mainly creatine measurements. However, given the mode of action of SGLT2 blockers, initiation of a therapy with a SGLT2 blocker will cause an increase of creatine because of its effects on the tubuloglomerular feedback mechanisms/glomerular hemodynamics like RAAS blocking agents do. To really understand the potential effects of SGLT2 inhibitors, we need preclinical and clinical SGLT2 inhibitor studies focusing on all aspects of acute kidney injury - not just changes in GFR biomarkers.
Gesehen am 01.10.2019